2019
DOI: 10.1002/cpdd.668
|View full text |Cite
|
Sign up to set email alerts
|

Study on Drug‐Drug Interactions Between Chiglitazar, a Novel PPAR Pan‐Agonist, and Metformin Hydrochloride in Healthy Subjects

Abstract: Chiglitazar (CHI) is a potent and selective peroxisome proliferator‐activated receptor potentially for the treatment of patients with type 2 diabetes mellitus (T2DM). An open‐label, randomized, 3‐period crossover and self‐controlled study was conducted to investigate drug‐drug interaction potential between CHI and metformin hydrochloride (MET). Eligible subjects received a single oral dose of CHI (48 mg), MET (1000 mg), or a combination in each period, followed by serial blood sampling collected for up to 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The plasma concentration of chiglitazar was determined by a validated high‐performance liquid chromatography coupled with tandem mass spectrometry method. Chiglitazar and the internal standard (the internal standard was the same as in the previous study 18 ) were extracted from plasma by protein precipitation. The analytes were eluted via a Luna C8 column (50 × 20 mm, 5 μm) with a varying gradient mobile phase of acetonitrile and 0.4% formic acid (pH 3.2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The plasma concentration of chiglitazar was determined by a validated high‐performance liquid chromatography coupled with tandem mass spectrometry method. Chiglitazar and the internal standard (the internal standard was the same as in the previous study 18 ) were extracted from plasma by protein precipitation. The analytes were eluted via a Luna C8 column (50 × 20 mm, 5 μm) with a varying gradient mobile phase of acetonitrile and 0.4% formic acid (pH 3.2).…”
Section: Methodsmentioning
confidence: 99%
“…Within 96 hours after oral administration of 3 H‐chiglitazar, the radioactivity excreted in urine and feces in rats was 25% and 66% of the dose, respectively. No significant inhibition and induction effect on drug‐metabolizing enzymes was found 18,21 . Previous clinical studies have shown that chiglitazar has favorable linear pharmacokinetic properties in healthy subjects following ascending single dosing of 8‐72 mg 21 and no significant pharmacokinetic drug‐drug interaction between chiglitazar and metformin 18 .…”
mentioning
confidence: 87%
See 2 more Smart Citations
“… ( a ) Predicted plasma concentrations of metformin following different dosage of human. ( b ) Predicted (line) and observed (point) relationship between metformin dose and dose/AUC for different dose; shaded area, 0.5–2.0 folds of prediction; observations were cited from [ 13 , 15 , 16 , 19 , 20 , 27 , 68 , 69 , 84 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. ( c ) Visual predictive checks (VPCs) of metformin plasma concentrations to time in 500 mg oral administration for human; solid line, the 50th percentiles; dashed lines, the 5 and 95th percentiles of the simulated populations; the shaded area, 90% confidence intervals of the simulated concentrations of the 5, 50 and 95th percentiles; and the point, observations, which were cited from [ 27 , 69 , 91 , 93 , 97 , 114 ].…”
Section: Figurementioning
confidence: 99%